Start-up Initiatives in Assam: Case Study on Five Successful Entrepreneurs of Assam - Sanjay Rizal, Suraj Das (International Journal of Advanced Science and Technology, 2020)
The state Assam is situated in the northeast of India. The state imparts its borders with Arunachal Pradesh, Nagaland, Manipur, Meghalaya, Mizoram, Tripura, and West Bengal. Assam is the gateway to Northeast India and acts as a vital link for trade with Southeast Asian nations. Though the state Is endowed with Tea, petroleum, Muga silk, and biodiversity still, the state has miles to go as number of natural resources are untapped here yet. Taking this into consideration, the government of Assam has launched “Startup Assam” in 2017 to inject innovative blood to the young aspirants of the state. The purpose of this paper is to identify the start-up initiatives taken in Assam and the determinants that stand as barriers during the developing stage of the business. To fulfill the objective of the paper, the researcher will take the case study of five successful entrepreneurs in Assam, and the data will be collected through a personal interview, telephonic interview, mail, or any other suitable sources. This paper will motivate and inspire the youths to go for something new and unique and will act as a pill to eradicate the pain of poverty in the state.